Precalculus: Concepts Through Functions, A Unit Circle Approach to Trigonometry (3rd Edition)

Published by Pearson
ISBN 10: 0-32193-104-1
ISBN 13: 978-0-32193-104-7

Chapter 3 - Polynomial and Rational Functions - Section 3.2 The Real Zeros of a Polynomial Function - 3.2 Assess Your Understanding - Page 225: 108



Work Step by Step

The factor theorem states that when $f(a)=0$, then we have $(x-a)$ as a factor of $f(x)$ and when $(x-a)$ is a factor of $f(x)$, then $f(a)=0$. As per the given equation, when $f(x)=x^4=kx^3+kx^2+1$ has a factor $x+2$, then by the factor theorem $f(-2)=0$. We simplify the given equation as follows: $f(-2)=(-2)^4-k(-2)^3+(-2)^2k+1=0 \\ 16+8k+4k+1=0\\ -12k =17 \\ k=\dfrac{-17}{12}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.